2006
DOI: 10.1534/genetics.105.054791
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Microsatellites in the Genome ofMedicago truncatula: A Resource of Genetic Markers That Integrate Genetic and Physical Maps

Abstract: Microsatellites are tandemly repeated short DNA sequences that are favored as molecular-genetic markers due to their high polymorphism index. Plant genomes characterized to date exhibit taxonspecific differences in frequency, genomic location, and motif structure of microsatellites, indicating that extant microsatellites originated recently and turn over quickly. With the goal of using microsatellite markers to integrate the physical and genetic maps of Medicago truncatula, we surveyed the frequency and distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
144
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(177 citation statements)
references
References 50 publications
29
144
4
Order By: Relevance
“…The genotypes were discriminated into two major clusters at 60 % similarity Physiol Mol Biol Plants (April-June 2016) 22(2):219-229 225 dataset was limited, low stringent conditions were applied to identify SSRs from sequences. The identified SSRs include both class I (C20 bp size) and class II (C 12 bp B 19 bp size) (Mun et al 2006) repeat motifs. The observed frequency of microsatellites in genomic DNA was 1.63 SSR/kbp (including hexa nucleotides with 12 bp size).…”
Section: Discussion Isolation Of Microsatellites and Enrichment Efficmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes were discriminated into two major clusters at 60 % similarity Physiol Mol Biol Plants (April-June 2016) 22(2):219-229 225 dataset was limited, low stringent conditions were applied to identify SSRs from sequences. The identified SSRs include both class I (C20 bp size) and class II (C 12 bp B 19 bp size) (Mun et al 2006) repeat motifs. The observed frequency of microsatellites in genomic DNA was 1.63 SSR/kbp (including hexa nucleotides with 12 bp size).…”
Section: Discussion Isolation Of Microsatellites and Enrichment Efficmentioning
confidence: 99%
“…In total 140 microsatellite repeats which include di, tri, tetra, penta and hexa repeat motifs were identified out of which 12 sequences had compound SSRs and all others were perfect repeats (Table 1, Online Resource 1). Among the repeats 27 were class 1 (C20 bp in size) and remaining were class 11 (C 12 bp B 19 bp) (Mun et al 2006). The size of the repeats varied from 10 to 54 bp.…”
Section: Identification Of Ssrs and Primer Designingmentioning
confidence: 99%
“…Comparative studies among several plant species, with a 50-fold range in genome size, revealed a positive relationship between genome size and the proportion of repetitive DNA (Morgante et al, 2002). It is interesting that SSRs were thought to be preferentially associated with the low-copy, gene-rich regions of Arabidopsis, corn, rice, soybean and wheat (Morgante et al, 2002), supported by a recent study of the model legume Medicago truncatula (Mun et al, 2006). These findings are reflected in the relatively high frequency of SSR transferability among legume species (Pandian et al, 2000;Gutierrez et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…Microsatellites are abundant within both animal and plant genomes (Temnykh et al, 2001;Morgante et al, 2002;Mun et al, 2006) and exhibit a high mutation rate, making them attractive as multiallelic, codominant and reliably scored molecular markers. In the most commonly used approach, sequence information of microsatellite-flanking regions is employed to design locusspecific PCR primer pairs to identify amplicon size polymorphism among genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, marker applications to assist breeding are reported both for herbaceous (Huang et al, 1996) and woody plants (Gianfranceschi et al, 1994;Akkurt et al, 2007). In plants, genetic markers provide the framework in breeding programs via marker-assisted selection (Mazur and Tingey, 1995), map-based cloning (Tanksley et al, 1995), and anchoring physical maps (Mun et al, 2006;Troggio et al, 2007). Among the wood plants, poplar (Populus trichocarpa Torr.…”
Section: Introductionmentioning
confidence: 99%